Aspectos financieros de las acciones nacionales de mitigación apropiada (NAMA) para los sistemas ganaderos en la región de América Latina y El Caribe - Otárola, M.; Sepúlveda, Claudia J.; Villanueva, C.; Solano, C.; Martínez Barón, Deissy; Arango, Jacobo; Román Cuesta, Rosa María (Centro Agronómico Tropical de Investigación y Enseñanza, 2021)
This document summarizes the results of the analysis on the financing issues related to business models proposed by existing NAMAs or emission reduction initiatives in nine LAC countries (Mexico, the Dominican Republic, Guatemala, Honduras, Costa Rica, Colombia, Argentina, Uruguay and Paraguay), developed between November 2018 and February 2019 by reviewing and analyzing secondary information and consulting (remotely) with key informants from each country evaluated. Financial and non financial barriers were evaluated, along with financial instruments proposed by livestock NAMAs. As a result, the implementation of a financing mechanism in countries developing NAMAs or livestock programs is recommended, as well as a few general recommendations to guide the financial aspects of these initiatives, in order to increase their long-term sustainability.